Methodologies for locating damage in prestressed concrete beams - Ercolani, Germán Darío; Ortega, Néstor Francisco; Felix, Daniel Horacio (Revista ALCONPAT, 2017)
This work evaluates methodologies for the detection of damage in prestressed concrete structures. The methods studied are the variation of the displacements and the curvature of the elastic, complemented by the use of thermographic images. To this end, these methods were applied on two prestressed concrete beams, built in the laboratory. The results obtained allowed to detect the presence of damage and to locate it with good precision. Although these methods have already been applied to reinforced concrete structures, no applications have been found to prestressed concrete structures. The effectiveness of the proposed methodologies was demonstrated and the possibility and convenience of a combined use of them are highlighted.